The effects of spirulina Platensis on the ethanol-induced Neurotoxicity - Ismail, Zul lzhar Mohd; Hossain, SM Akram; Asari, Mohd Asnizam (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Spirulina is a blue-green alga (cyanobacterium) that has been consumed as food since ancient times. Nowadays, spirulina is widely marketed as a food supplement (nutraceutical) as it is believed to have many therapeutic benefits. Many of the therapeutic benefits of spirulina are believed to be due to its high anti-oxidative activity. Studies have shown that intermittent binge-like ethanol consumption during adolescent period causes neuronal damage in specific parts of the brain. It has been suggested that antioxidant therapy may provide some level of protection against neurotoxicity of ethanol at cellular level and genomic level. Therefore, the purpose of this study was to examine the protective effects of spirulina supplementation against ethanol-induced neurotoxicity in the brain of adolescent rats. Male Sprague-Dawley rats were given ethanol (10 g/kg/day, intermittent binge model), Spirulina platensis (1000 mg/kg/day) or both from postnatal day 30 for two weeks. The cerebral hemispheres were processed for routine histological staining and immunohistochemistry with anti-GFAP and anti-synaptophysin antibodies. Ethanol-treated group showed significant deficit in the numbers of neurons (per mm2 ) in the CA 1 and CA3 region of the hippocampus and also in the granule cell layer and hilar regions of the dentate gyrus. Spirulina supplementation failed to provide protection against ethanol-induced neuronal loss in these regions. Spirulina supplementation also failed to alter increased expression of GFAP immunoreactivity induced by ethanol exposure. In conclusion, these findings indicate that spirulina supplementation was not effective in reducing the ethanolinduced neurotoxicity in the hippocampus and dentate gyrus of rats.